Commitment and Cost of Equity Capital: An Examination of Timely Balance Sheet Disclosure in Earnings Announcements - Evans, Mark E. (Contemporary Accounting Research, 2016)
Abstract In this paper, I examine the relation between disclosure commitment and cost of equity capital using accelerated earnings announcement disclosures as a measure of commitment. In settings characterized by imperfect market competition, I find that firms which consistently disclose balance sheet detail in relatively timely earnings announcements have lower costs of capital compared to other firms. This result is statistically significant and economically meaningful, and is robust to various alternative measurements for cost of capital, and alternative designs addressing endogeneity and underlying information quality. Overall, this result is important because it highlights additional dimensions of disclosure commitment (consistency and timeliness), while incorporating important features from theoretical models (information quality and market competition). In particular, my results suggest that consistency and timeliness are salient features of firms' disclosure behavior that have predictable and robust relations with capital market outcomes. This result is robust to controlling for underlying information quality; however, consistent with theory, it is conditional on low levels of market competition.